In Vivo Study of Effect of C60 Fullerene Aqueous Colloidal Solution on Membrane State and Biochemical Indices - Vlasov, Aleksandr A.; Panov, Sergey I.; Kovalev, Gennadiy A.; Byelochkina, Irina V.; Nipot, Elena E.; Shpakova, Natalia M.; Yefimova, Irina O.; Sandomirsky, Boris P. (Problems of Cryobiology and Cryomedicine, 2015)
N/A